PI Controller Design for Time Delay Systems Using an Extension of the Hermite-Biehler Theorem. (16th December 2012) - Elmadssia, Sami; Saadaoui, Karim; Benrejeb, Mohamed
Abstract : We consider stabilizing first-order systems with time delay. The set of all stabilizing proportional-integral PI controllers are determined using an extension of the Hermite-Biehler theorem. The time delay is approximated by a second-order Padé approximation. For uncertain plants, with interval type uncertainty, robust stabilizing PI controllers are determined.